(3UHG fLO aj GdhYXs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3eMeO Hf EHQGgje s)
(3ChdgG (B:s
(3GdMeO ddg Ydi efMg GdJi JahJ GdEMUGA hGdYO gPG cJGH jRjO Ydi fSje GdUHG QbI hefGOHge jfTO jGdjJ eG cGf bW de jcf s
(3BNQgG (B:s
(3jfJgi HGdaUd GdKGdK hGdCQHYhf jG ScGf GdeRGHd CeG JDKQhf YdjgG eSGcf WjHI s
(3fSNI fajSI LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1070s
Keywords: (3GdJUha hGdBOGH GdTQYjIs